Structure analysis of advanced nanomaterials : nanoworld by high-resolution electron microscopy - Oku, Takeo, 1965- (De Gruyter, 2014)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> High-resolution electron microscopy allows the imaging of the crystallographic structure of a sample at an atomic scale. It is a valuable tool to study nanoscale properties of crystalline materials such as superconductors, semiconductors, solar cells, zeolite materials, carbon nanomaterials or BN nanotubes.